Gamma-radiation induced degradation random walk error in interferometer fiber optic gyroscope - Du, Shisen; Wang, Xueqin; Lin, Song; Zhang, Chunxi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Gamma-radiation induced random walk error (RWE) of interferometer fiber optic gyroscope (IFOG) is presented in this paper. Testing was performed at the components and system level with an expanded version of a closed-loop operational fiber optic gyroscope. Primary concerns include attenuation to total dose, angle random walk, and bias stability degradation as a function of dose. Closed-loop transient noise results are evaluated based on radiation test of the 400 m fiber coil. Based on the test result, a random walk coefficient (RWC) prediction model in radiation environment, which is obtained by embedding polarization-maintaining (PM) fiber loss expression into the RWC model, was built following a power law of dose. An IFOG RWC in space radiation environment was predicted from radiation dose rate by the prediction model. The RWC of the IFOG is limited by the detector thermal noise above 1 kGy radiation and the RWC prediction model is verified by radiation experiment.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 953-959
Keywords: optyka; fiber optic gyroscope; gamma radiation; noise; random walk coefficient